Evaluation Of Team Compliance To Apply WHO Surgical Safety Checklist On Major Surgical Operation In Surgical Department Of PKU Muhammadiyah Bantul Hospital - Karlina, Siti (Archives of Business Research, 2018)
Background: Procedure of major surgery at PKU Muhammadiyah Bantul Hospital already has a standard from medical committee in surgical department, but there is no evaluation to assess safety related to surgical procedure. Aim: To assess surgical team compliance to apply surgical safety checklist, especially part of sign in, time out, and sign out phase at major surgery and to find strategy to minimize obstacles about implementation of surgical safety checklist in operating room of PKU Muhammadiyah Bantul Hospial. Method: This study using sequential explanatory design. The subjects were all staffs who were work in the operating room, then nurse and doctor were assessed about surgical safety checklist including sign in, time out and sign out. Data collection was done gradually for 7 days in the surgery instalation of PKU Muhammadiyah Bantul Hospital. Instrument: This study used WHO surgical safety checklist which was divided into three phases: before induction (Sign In), before the skin incision (Time Out), and before the patient leaves the operating room (Sign Out). If the procedure is not completely done then the point is 0 and if completely done the point is 1. Result: There were 30 surgery sessions in urology surgery 7 (23,33%), obgyn 6 (20%), orthopedic 2 (6,67%), oncology 3 (10%), digestive 6 (20%), and other operations 6 (20%). The lowest compliance to filling the checklis was the time of sign in 4 (13.3%) of 30 operating sessions. The lowest compliance during time out was filling the time that was only filled as much as 3 (10%), and insertion of radiology imaging that was just as much as 5 (16,7%). The lowest compliance when signed out was the time of sign out (10,0%) and post op diagnosis (16,7%). Conclusion: Surgical Safety Checklist filling either Sign In, Time Out, or Sign Out at Surgery Instalation PKU Muhammadiyah Bantul Hospital was included in less obedient criteria.